Bacteria-driven peribronchial lymphoid neogenesis in bronchiectasis and cystic fibrosis. Issue 4 (27th April 2017) - Frija-Masson, Justine; Martin, Clémence; Regard, Lucile; Lothe, Marie-Noëlle; Touqui, Lhousseine; Durand, Aurélie; Lucas, Bruno; Damotte, Diane; Alifano, Marco; Fajac, Isabelle; Burgel, Pierre-Régis
We aimed to characterise lymphoid neogenesis in bronchiectasis and cystic fibrosis (CF) lungs and to examine the role of bacterial infection. Lymphoid aggregates were examined using immunohistochemical staining and morphometric analysis in surgical lung sections obtained from nonsmokers and patients with bronchiectasis or CF. Sterile, Pseudomonas aeruginosa - or Staphylococcus aureus -coated agarose beads were instilled intratracheally in mice. Kinetics of lymphoid neogenesis and chemokine expression were examined over 14 days. Lymphoid aggregates were scarce in human lungs of nonsmokers, but numerous peribronchial lymphoid aggregates containing B-lymphocytes, T-lymphocytes, germinal centres and high endothelial venules were found in bronchiectasis and CF. Mouse lungs contained no lymphoid aggregate at baseline. During persistent P. aeruginosa or S. aureus airway infection peribronchial lymphoid neogenesis occurred. At day 14 after instillation, lymphoid aggregates expressed markers of tertiary lymphoid organs and the chemokines CXCL12 and CXCL13. The airway epithelium was an important site of CXCL12, CXCL13 and interleukin-17A expression, which began at day 1 after instillation. Peribronchial tertiary lymphoid organs are present in bronchiectasis and in CF, and persistent bacterial infection triggered peribronchial lymphoid neogenesis in mice. Peribronchial localisation of tertiary lymphoid organs and epithelial expression of chemokines suggest roles for airway epithelium in lymphoid neogenesis. Bacterial infection-induced peribronchial lymphoid neogenesis in bronchiectasis and CF may involve airway epithelium http://ow.ly/pDMB308a3B0